Medieval Georgian Poliorcetica - TSURTSUMIA, Mamuka (Historia i Świat, 2015)
In the medieval art of war siege constituted one of the principal forms of fight. Several basic techniques were used in taking a stronghold, such as assaulting the walls of the fortress, breaching the wall, digging a subterranean tunnel under the wall and enfeeblement of the garrison by lengthy siege. Bearing in mind various data, in the Middle Ages Georgians used the following technical means to capture fortresses: assault ladders, battering rams and other engines for breaching walls, ballistas, stone throwing engines and subterranean tunnels. In the article light is shed on the siege capabilities of the Georgian army of the period. Extensively discussed are the Georgian army’s stone throwing artillery, various types of stone hurling engines and the time of their spread in Georgia. Various techniques of capturing fortresses, applied by the Georgians are described. These include mounting the walls with ladder or various improvised means. The hazardous technique of directly assaulting the fortress without preliminary preparation or bringing up heavy siege engines is shown. The capturing of fortresses by means of underground tunnels is discussed separately. By the available evidence it is not apparent that Georgians made use of all the siege techniques known in the medieval world; however, it can be said that they were familiar with and used successfully the basic methods of siege warfare.